Exploring the decision component of the Activation-Decision-Construction-Action Theory for different reasons to deceive - Cassidy, Hannah (Legal and criminological psychology, 2019)
Objectives. To explore how reasons to lie impact upon the decision component of Activation-Decision-Construction-Action Theory. Design. Specifically, the study looked at how beneficiary of the lie (self vs. another) and additional cost of lying (no cost vs. cost to self/other) might influence decisions to lie. Methods. Ninety-one undergraduate students read four hypothetical scenarios representing the four reasons to lie. They stated whether they would decide to tell the truth/lie for each scenario and also estimated the probability and valence of being believed, or not, if they did decide to tell the truth/lie. These estimations were inputted into the ADCAT formulae. Results. Higher expected values of truth-telling only reduced likelihood to decide to lie when the lie benefitted another. Beneficiary of the lie and additional cost together did not moderate any of the relationships between the ADCAT variables and hypothetical decisions to lie. However, the additional cost (e.g., to self or another) was a significant predictor of anticipated lying behaviour. The more likely there was a cost to self or other, the less likely the participants were to decide to lie. Conclusions. Weighing up the expected cost and benefits of truth-telling and lying was associated with hypothetical decisions to lie or not. However, other variables, such as additional cost to self or another, should be considered in the ADCAT model to extend our understanding of this decision-making process. Future research is required to investigate whether these relationships can be manipulated to promote honesty and deter deceit.